Liver Transplantation and Quality of Life. (1st September 2000) - Rodés, J; Navasa, M
Abstract : To date, more than 50, 000 liver transplantations have been performed around the world; the survival rate five years after transplantation ranges from 60% to 65%. One of the fundamental objectives for liver transplantation teams is to achieve the best possible quality of life (QOL) for the patients. A concise analysis of the methodology used (15 questionnaires) to measure QOL of patients with liver transplants is described. The authors suggest that now is the time to establish a database so that a validated instrument will be available to compare QOL results from all the liver transplantation programs. Liver transplantation is believed to improve QOL, although there are several problems with some of the papers published on this subject. Some studies are retrospective, whereas in others, patients in bad physical conditions are excluded from the study; in quite a few prospective studies, deaths are not included in the data analysis. Finally, the authors provide a brief, concise analysis of late complications and of recurrence of the disease after liver transplantation, which influence QOL.